PREFERENSI KONSUMEN TERHADAP SAYURAN ORGANIK DI PASAR MODERN KOTA MALANG - Pebryanto, Alfredo; Pudjiastuti, Agnes Quartina; Sa'diyah, Ana Arifatus (Fakultas Pertanian, 2017)
This study aims to examine consumer preferences and attributes most considered by consumers in the decision to purchase organic vegetables in the Modern Market of Malang City. The analytical method used is the analysis of Chi Square and Fishbein Multiattributes. Organic vegetables that become consumer preferences in the Modern Market in Malang City are successively, for spinach vegetables are fresh vegetables, color, packaging, physical perfection and taste. for mustard vegetables are fresh vegetables, color, taste, physical perfection and packaging. The attributes of organic vegetables that are considered by consumers in the decision to purchase vegetables in the Modern Market in Malang City are the freshness of vegetables. Penelitian ini bertujuan untuk mengkaji preferensi konsumen dan atribut yang paling dipertimbangkan oleh konsumen dalam keputusan pembelian sayuran organik di Pasar Modern Kota Malang. Metode analisis yang digunakan yaitu analisis Chi Square dan Multiatribut Fishbein. Sayuran organik yang menjadi preferensi konsumen di pasar Modern Kota Malang secara berturut-turut adalah, untuk sayuran bayam adalah kesegaran sayuran, warna, kemasan, kesempurnaan fisik dan rasa. Atribut sayuran organik yang menjadi pertimbangan konsumen dalam keputusan pembelian sayuran di Pasar Modern Kota Malang adalah kesegaran sayuran.